SOCIAL CONNECTEDNESS AS A BUFFER FOR MENTAL HEALTH CHALLENGES IN TRANSGENDERS - Amir Ahmad; Humera Shafi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The current study set out to examine and evaluate the connection between transgender people's mental health and social connectedness. The sample consisted of seventy-seven transgenders from various parts of Kashmir. The instruments utilized for assessing social connectedness and mental health were the revised social connectedness scale, 1998 and the general health questionnaire, 1988, respectively. Findings of the study, revealed that social connectedness was positively and significantly correlated with mental health among transgenders, indicating that higher levels of social connectedness are associated with better mental health outcomes. Furthermore, participants from rural and urban areas did significantly differ in terms of social connectedness and mental health, with rural transgenders having lower social connectedness while also experiencing poor mental health outcomes, emphasizing the need for targeted support interventions for those in rural areas.